Multi-gradient nanofiber membrane as well as preparation method and application thereof
The multi-gradient nanofiber membrane prepared by electrospinning technology uses the multi-gradient structure of MgO/MgCO3/PCL to achieve the sustained release of Mg2+, which solves the problems of limited autologous nerve sources and large surgical trauma in peripheral nerve injury repair, and significantly promotes Nerve regeneration and repair effects.
Patent Information
- Application Number
- CN202411300921.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The prior art has problems such as limited autologous nerve sources, large surgical trauma, and many complications in the repair of peripheral nerve damage, and the existing biomaterial bridging technology is difficult to effectively promote nerve regeneration.
A multi-gradient nanofiber membrane is used to prepare a three-layer MgO/MgCO3/PCL membrane through electrospinning technology. The proportion of MgO and MgCO3 in each layer gradually decreases from the inner layer to the outer layer, forming a multi-gradient structure to achieve Mg2+ relaxation. Release and promote nerve regeneration.
The multi -gradient nano -fiber membrane has excellent biocompatibility and controllable mechanical properties. It can continuously and effectively release MG2+during the treatment, significantly promote nerve regeneration, reduce surgical trauma and complications, and improve peripheral nerve repair effects.
Smart Images

Figure CN119332411A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterials, and in particular to a multi-gradient nanofiber membrane and a preparation method and application thereof. Background Art
[0002] Peripheral nerve defect refers to a clinical condition in which the peripheral nerve trunk or its branches are accidentally damaged by direct or indirect external trauma (such as trauma, tumors, and other factors), resulting in motor, sensory, and autonomic dysfunction of the trunk and limbs. If not effectively treated, it will affect the structural development of the affected limbs, thereby affecting life, study, and work, and also have a certain impact on psychological development. Peripheral nerve injury is mainly manifested as motor dysfunction, sensory dysfunction, and neurotrophic changes. Most patients require surgical treatment. Some patients can be cured, but a few patients are disabled for life. In addition, peripheral nerve defects often occur in young and middle-aged people. The loss of individual labor force and high rehabilitation costs caused by them bring huge economic losses to society and families.
[0003] Nerve defects usually require nerve transplantation or bridging with various biomaterials to repair. Autologous nerve transplantation is currently the gold standard for clinical treatment, which requires surgery to use a section of nerve tissue to bridge the gap between the damaged nerve ends. Although autologous nerve transplantation is still the first choice for clinical treatment, the source of autologous nerves is limited. Removing autologous nerves not only increases surgical trauma, but also causes complications such as scars in the surgical area, painful neuroma formation, and dysfunction in the innervated area. Therefore, designing and preparing new nerve grafts and exploring their key mechanisms for promoting nerve regeneration are of great clinical research significance for improving the effect of peripheral nerve repair. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a multi-gradient nanofiber membrane and a preparation method and application thereof.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] In the first aspect, the present invention provides a multi-gradient nanofiber membrane, comprising an inner layer, a middle layer and an outer layer; the inner layer comprises a magnesium-containing compound and polycaprolactone in a mass ratio of (0.12-0.36):1; the middle layer comprises a magnesium-containing compound and polycaprolactone in a mass ratio of (0.1-0.3):1; the outer layer comprises a magnesium-containing compound and polycaprolactone in a mass ratio of (0.08-0.24):1.
[0007] The multi-gradient nanofiber membrane of the present invention is a three-layer structure, and its design takes into account many factors, reduces confounding factors, controls variables, and focuses on Mg 2+Changes in downstream gene expression caused by sustained release. PCL was mixed with magnesium-containing monomers of different concentrations to form multi-layer nanofiber conduits. The weight ratio of MgO and MgCO3 in each layer gradually decreased from the inner layer to the outer layer. The composition of Mg monomers showed layer-dependent changes, with the inner layer containing the most MgCO3 and the outer layer containing the most MgO. The difference in the concentration and composition of Mg monomers ultimately formed a multi-gradient structure of the three layers of electrospun membranes, which in turn affected the Mg 2+ The release efficiency and biocompatibility of the catheter can be continuously and effectively released during the treatment period, thereby promoting nerve regeneration, and an effective controlled release carrier is used to optimize its in vivo therapeutic effect. It can be applied to the repair of peripheral nerve injuries, and it is safe and effective, not only acting on the early stage of nerve regeneration, but also affecting the middle and late stages of nerve repair.
[0008] In addition, the MgO / MgCO3 / PCL multi-gradient nanofiber membrane of the present invention helps to improve the mechanical properties of implants, is used to simulate the environment of natural neural tissue, and optimizes the migration and growth of neural cells.
[0009] As a preferred embodiment of the multi-gradient nanofiber membrane of the present invention, the magnesium-containing compound includes MgO and MgCO3.
[0010] As a further preferred embodiment of the multi-gradient nanofiber membrane described in the present invention, the mass ratio of MgO and MgCO3 in the inner layer is (0.3-0.7):1; the mass ratio of MgO and MgCO3 in the middle layer is (0.8-1.4):1; the mass ratio of MgO and MgCO3 in the outer layer is (1.5-2.5):1.
[0011] Preferably, the mass ratio of MgO and MgCO3 in the inner layer is 0.5:1; the mass ratio of MgO and MgCO3 in the middle layer is 1:1; and the mass ratio of MgO and MgCO3 in the outer layer is 2:1.
[0012] As a preferred embodiment of the multi-gradient nanofiber membrane described in the present invention, the mass percentage of magnesium in the inner layer is 12.57%-24.54%; the mass percentage of magnesium in the middle layer is 11.42%-20.46%; and the mass percentage of magnesium in the outer layer is 9.43%-19.63%.
[0013] In a second aspect, the present invention provides a method for preparing the multi-gradient nanofiber membrane, comprising the following steps:
[0014] (1) adding the polycaprolactone into a solvent and stirring to obtain a mixed solution;
[0015] (2) adding the magnesium-containing compound to the inner layer, the middle layer and the outer layer respectively, stirring evenly, and obtaining the electrospinning solutions of the inner layer, the middle layer and the outer layer respectively;
[0016] (3) The obtained electrospinning solutions of the inner layer, the middle layer and the outer layer are used for electrospinning, and the electrospinning is stacked layer by layer to form an electrospun membrane with a three-layer composite structure, that is, a multi-gradient nanofiber membrane.
[0017] The preparation method of the present invention uses electrospinning technology to prepare a long-acting sustained-release Mg 2+ Multi-gradient nanofiber membranes for single-channel nerve conduits with rational and effective Mg 2+ The sustained-release system regulates the local nerve regeneration microenvironment and promotes the transformation of SCs to a repair phenotype to repair peripheral nerve defects. It can achieve effective Mg release for 4-6 weeks. 2+ Sustained release.
[0018] As a preferred embodiment of the preparation method of the present invention, in step (1), the solvent is trifluoroethanol; the mass volume ratio of the polycaprolactone to the solvent is 5%-15% g / mL.
[0019] As a preferred embodiment of the preparation method of the present invention, in step (3), the electrospinning adopts a high voltage electric field of 10kv-20kv.
[0020] In a third aspect, the present invention provides a nerve conduit having the multi-gradient nanofiber membrane built therein.
[0021] As a preferred embodiment of the nerve guide of the present invention, the inner layer of the multi-gradient nanofiber membrane faces the inner wall of the nerve guide.
[0022] In a fourth aspect, the present invention uses the multi-gradient nanofiber membrane and the nerve conduit in any of the following fields, including:
[0023] i. Preparation of preparations for promoting nerve regeneration;
[0024] ii. preparing a nerve conduit for promoting nerve regeneration;
[0025] iii. Preparation of preparations for peripheral nerve defect repair;
[0026] iv. Preparation of nerve conduits for peripheral nerve defect repair;
[0027] v. Treatment of peripheral nerve defects for purposes other than diagnosis or treatment of other diseases.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The nanofiber membrane or multi-gradient nanofiber membrane of the present invention has excellent biocompatibility, controllable mechanical properties and degradation characteristics. It is applied to the repair of peripheral nerve defects, which not only has significant therapeutic potential, but also shows extremely high scientific research value. It provides an important theoretical basis for the promotion and application of magnesium-containing nerve stent repair.
[0030] 2. Aiming at the limitations and complications of autologous nerves and magnesium-containing nerve stents, the present invention solves the following technical problems: 1) Source limitation problem: The preparation method of the present invention is simple, low-cost, with sufficient raw materials, high efficiency, mass production, wide adaptability and strong compatibility; 2) Surgical trauma and complications: The present invention does not require additional surgical trauma, postoperative pain, donor scar formation, painful neuroma formation and nerve innervation area dysfunction; 3) Mg 2+ Long-acting sustained release problem: The present invention can achieve 4-6 weeks of effective Mg release according to different magnesium concentrations. 2+ Sustained release.
[0031] 3. The present invention uses this nerve conduit to repair a 10 mm sciatic nerve defect in rats, and detects high expression of the SCs phenotype conversion characteristic gene C-Jun, which can significantly promote the myelination of regenerated axons and reinnervation of muscle tissue compared with autologous nerve repair. 2+ The role of magnesium in the phenotypic conversion of Schwann cells during nerve regeneration was studied by using transcriptome sequencing and single-cell sequencing to detect key upstream and downstream genes, screen specific cell types and key signal pathways that respond to magnesium-containing scaffold materials during peripheral nerve regeneration, and reveal the molecular mechanism by which magnesium-containing scaffold materials promote peripheral nerve repair. This invention is innovative in method and fully explores the role of magnesium in the phenotypic conversion of Schwann cells during nerve regeneration. 2+ The regulation of various key cells in the process of nerve regeneration provides an important theoretical basis for the clinical transformation of magnesium-containing biomaterials repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the technical route flow of the present invention.
[0033] FIG2 is a scanning electron microscope scan and energy dispersive X-ray spectroscopy analysis of MgO / MgCO3 / PCL film; in the figure, Figure 2A SEM images of vertical structural features of MgO / MgCO3 / PCL membrane; Figure 2B , C, and D are EDS analysis and mapping of the inner, middle, and outer layers of the MgO / MgCO3 / PCL multi-gradient nanofiber membranes of Examples 1-3, respectively, which confirm the existence of the multi-gradient structure and show a trend of gradually decreasing Mg element proportion from the inner layer to the outer layer.
[0034] FIG3 shows the fabrication and characterization of MgO / MgCO3 / PCL multi-gradient nanofiber membranes; Figure 3A Schematic diagram of the manufacturing process of MgO / MgCO3 / PCL multi-gradient nanofiber membrane; Figure 3B Cumulative release of Mg from MgO / MgCO3 / PCL multi-gradient nanofiber membrane within 6 weeks 2+ ; Figure 3C SEM characterization of MgO / MgCO3 / PCL multi-gradient nanofiber membrane; Figure 3D To calculate the diameter of nanofibers; Figure 3E To measure the contact angle of MgO / MgCO3 / PCL multi-gradient nanofiber membrane.
[0035] FIG4 shows H&E analysis and remyelination of regenerated nerves; in the figure, Figure 4A Schematic diagram of animal surgery; Figure 4B For harvested regenerated nerves; Figure 4C H&E staining of the autologous graft, PCL nerve conduit, 10% MgO / MgCO3 / PCL, 20% MgO / MgCO3 / PCL, and 30% MgO / MgCO3 / PCL groups; Figure 4D is the diameter of the regenerated nerve (μm) (n=4); Figure 4E Toluidine blue staining and TEM analysis of remyelinated axons were performed on transverse sections of grafts harvested 12 weeks after surgery; Figure 4F is the diameter of myelinated axons (μm) (n=5); Figure 4G is the number of myelinated axons (n=5); Figure 4H is the thickness of the newly formed myelin sheath (μm) (n=5).
[0036] FIG5 shows the functional recovery analysis evaluated by SFI value, electrophysiological evaluation and Masson staining of triceps calf muscle cross-sectional samples; Figure 5A Schematic diagram for calculating SFI value; Figure 5B The SFI values for all groups gradually increased over time, showing partial recovery of function at 6 and 12 weeks after surgery (n=5); Figure 5C The CAMP amplitude of the five groups 12 years after surgery; Figure 5D is the CAMP amplitude (unit: mV) (n=4); Figure 5E Masson staining of three calf muscle samples 12 years after surgery; Fig. 5F is the cross-sectional area of the muscle fiber; Figure 5G is the cross-sectional area of collagen fibers; Figure 5H is the percentage of collagen fiber area (n=4); Fig.5I is the G ratio; data are expressed as mean ± standard deviation. Statistical analysis was performed using one-way analysis of variance (ANOVA) and Tukey test. DETAILED DESCRIPTION
[0037] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0038] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial sources. The data were analyzed using one-way ANOVA and Tukey's post-test, and are expressed as mean ± SD, *P < 0.05; **P < 0.01.
[0039] Example 1: Long-acting sustained-release Mg 2+ Preparation of electrospun membranes
[0040] Polycaprolactone PCL (Product No. 178301000, Thermofisher) was mixed with different concentrations of magnesium-containing monomers (MgO (Product No. 529699, Sigma), MgCO3 (Product No. 63032, Sigma)) and processed into multilayer nanofiber catheters using electrospinning technology. The specific steps are:
[0041] (1) Add 3 g of polycaprolactone to 30 mL of trifluoroethanol solvent and stir to obtain a mixed solution with a concentration of 10% by mass volume;
[0042] (2) adding a magnesium-containing monomer accounting for 10% by weight of polycaprolactone and stirring evenly to obtain a polycaprolactone magnesium-containing monomer electrospinning solution for a middle layer;
[0043] (3) preparing electrospinning solutions of polycaprolactone magnesium-containing monomers for the inner layer and the outer layer respectively;
[0044] Compared with the middle layer, the mass concentration of the magnesium-containing monomer in the inner layer and the outer layer increases by 20% (the magnesium-containing monomer accounts for 12% of the mass percentage of polycaprolactone) and decreases by 20% (the magnesium-containing monomer accounts for 8% of the mass percentage of polycaprolactone), respectively, so that the weight ratio of MgO and MgCO3 to PCL gradually decreases from the inner layer to the outer layer; wherein, the mass ratio of MgO and MgCO3 changes layer by layer as follows: 1:2 for the inner layer, 1:1 for the middle layer, and 2:1 for the outer layer;
[0045] (4) Using a 15 kV high voltage electric field, the inner, middle and outer three-layer polycaprolactone magnesium-containing monomer electrospinning solution was electrospun (TL-01, Tongli Technologies Co., China), and the electrospinning was stacked layer by layer to form a three-layer composite structure electrospun membrane, which was recorded as 10% MgO / MgCO3 / PCL multi-gradient nanofiber membrane.
[0046] Example 2: Long-acting sustained-release Mg 2+ Preparation of electrospun membranes
[0047] Polycaprolactone PCL (178301000, Thermofisher) was mixed with different concentrations of magnesium-containing monomers (MgO (529699, sigma), MgCO3 (63032, sigma)) and processed into multi-layer nanofiber catheters using electrospinning technology. The specific steps are:
[0048] (1) Add 3 g of polycaprolactone to 30 mL of trifluoroethanol solvent and stir to obtain a mixed solution with a concentration of 10% by mass volume;
[0049] (2) adding a magnesium-containing monomer accounting for 20% by weight of polycaprolactone and stirring evenly to obtain a polycaprolactone magnesium-containing monomer electrospinning solution for a middle layer;
[0050] (3) preparing electrospinning solutions of polycaprolactone magnesium-containing monomers for the inner layer and the outer layer respectively;
[0051] Compared with the middle layer, the mass concentration of magnesium-containing monomers in the inner layer and the outer layer increased by 20% (magnesium-containing monomers accounted for 24% of the mass percentage of polycaprolactone) and decreased by 20% (magnesium-containing monomers accounted for 16% of the mass percentage of polycaprolactone), respectively, so that the weight ratio of MgO and MgCO3 to PCL gradually decreased from the inner layer to the outer layer; wherein, the mass ratio of MgO and MgCO3 changed layer by layer as follows: 1:2 for the inner layer, 1:1 for the middle layer, and 2:1 for the outer layer;
[0052] (4) Using a 15 kV high voltage electric field, the inner, middle and outer three-layer polycaprolactone magnesium-containing monomer electrospinning solution was electrospun (TL-01, Tongli Technologies Co., China), and the electrospinning was stacked layer by layer to form a three-layer composite structure electrospun membrane, which was recorded as 20% MgO / MgCO3 / PCL multi-gradient nanofiber membrane.
[0053] Example 3: Long-acting sustained-release Mg 2+ Preparation of electrospun membranes
[0054] Polycaprolactone PCL (178301000, Thermofisher) was mixed with different concentrations of magnesium-containing monomers (MgO (529699, sigma), MgCO3 (63032, sigma)) and processed into multi-layer nanofiber catheters using electrospinning technology. The specific steps are:
[0055] (1) Add 3 g of polycaprolactone to 30 mL of trifluoroethanol solvent and stir to obtain a mixed solution with a concentration of 10% by mass volume;
[0056] (2) adding a magnesium-containing monomer accounting for 30% by weight of polycaprolactone and stirring evenly to obtain a polycaprolactone magnesium-containing monomer electrospinning solution for the middle layer;
[0057] (3) preparing electrospinning solutions of polycaprolactone magnesium-containing monomers for the inner layer and the outer layer respectively;
[0058] Compared with the middle layer, the mass concentration of magnesium-containing monomers in the inner layer and the outer layer increased by 20% (magnesium-containing monomers accounted for 36% of the mass percentage of polycaprolactone) and decreased by 20% (magnesium-containing monomers accounted for 24% of the mass percentage of polycaprolactone), respectively, so that the weight ratio of MgO and MgCO3 to PCL gradually decreased from the inner layer to the outer layer; wherein, the mass ratio of MgO and MgCO3 changed layer by layer as follows: 1:2 for the inner layer, 1:1 for the middle layer, and 2:1 for the outer layer;
[0059] (4) Using a 15 kV high voltage electric field, the inner, middle and outer three-layer polycaprolactone magnesium-containing monomer electrospinning solution was electrospun (TL-01, Tongli Technologies Co., China), and the electrospinning was stacked layer by layer to form a three-layer composite structure electrospun membrane, which was recorded as 30% MgO / MgCO3 / PCL multi-gradient nanofiber membrane.
[0060] like Figure 2A As shown in the figure, multilayer nanofibrous membranes were synthesized using PCL and different concentrations of magnesium monomers (MgO and MgCO3). Using electrospinning technology, a series of membranes composed of MgO / MgCO3 / PCL were created. Each membrane consists of 3 layers, and the ratio of MgO / MgCO3 decreases layer by layer, and the concentration of Mg monomer gradually decreases from the inside to the outside. It is worth noting that the ratio of Mg monomers in the three layers is different, with the inner layer containing more MgCO3 and the outer layer containing more MgO, thus forming a multi-gradient structure ( Figure 3A ).
[0061] Experimental Example 1: Evaluation of the performance of MgO / MgCO3 / PCL multi-gradient nanofiber membranes
[0062] The PCL electrospun membrane was set as the control group, the 10% MgO / MgCO3 / PCL multi-gradient nanofiber membrane of Example 1 was set as the 10% MgO / MgCO3 / PCL group, the 20% MgO / MgCO3 / PCL multi-gradient nanofiber membrane of Example 2 was set as the 20% MgO / MgCO3 / PCL group, and the 30% MgO / MgCO3 / PCL multi-gradient nanofiber membrane of Example 3 was set as the 30% MgO / MgCO3 / PCL group.
[0063] (1) Scanning electron microscopy and energy dispersive X-ray spectroscopy analysis of MgO / MgCO3 / PCL films.
[0064] Scanning electron microscopy (SEM) analysis revealed an interconnected network morphology consisting of nanofibers, in which MgO / MgCO3 nanoparticles with multiple gradient concentrations were well distributed in the three-layer structure. The cross-sectional SEM image showed the tight integration of the three-layer structure ( Figure 2A ).
[0065] Energy dispersive X-ray spectroscopy (EDS) analysis of different layers of each group of MgO / MgCO3 / PCL membranes confirmed the existence of a multi-gradient structure, showing a trend of a gradual decrease in the proportion of Mg elements from the inner layer to the outer layer ( Figures 2B to 2D ). The existence of the multi-gradient structure was verified by integrating cross-sectional SEM images and EDS analysis.
[0066] (2) The degradation performance of MgO / MgCO3 / PCL electrospun membrane was evaluated by in vitro degradation test incubated at 37°C.
[0067] The steps of the in vitro degradation test with incubation at 37°C refer to the scientific research literature Biosynthesized bandages carrying magnesium oxide nanoparticles induce cortical bone formation by modulating endogenous periosteal cells. ACS nano, 2022, 16(11): 18071-18089.
[0068] The Mg content in the solution was determined by inductively coupled plasma emission spectrometry (ICP-9820, Schimdzu, Japan). 2+ concentration, and plot Mg 2+ sustained release curve.
[0069] Mg 2+ The sustained release curve of Figure 3B Shown: Mg release in 10% MgO / MgCO3 / PCL group 2+ The most effective and stable release time is 1-6 weeks, and it reaches a plateau after 7 weeks. The release rate of the 20% MgO / MgCO3 / PCL group and the 30% MgO / MgCO3 / PCL group within 8 weeks is slower than that of the 10% MgO / MgCO3 / PCL group, and it did not reach the MgO / MgCO3 / PCL level within the detection time (within 8 weeks). 2+ Release peak.
[0070] The above results show that MgO / MgCO3 / PCL multi-gradient nanofiber membrane can achieve Mg 2+Adjustable and sustained release of MgO can be effectively regulated by adding different proportions of fast-degrading MgO and slowly-degrading MgCO3 to the inner, middle and outer layers of the MgO / MgCO3 / PCL multi-gradient nanofiber membrane. 2+ The release of MgCO3 can affect the sustained release performance of multi-gradient nanofiber membranes. 2+ The release of MgO / MgCO3 / PCL in the 20% and 30% groups was weaker than that in the 10% MgO / MgCO3 / PCL membrane during the first 8 weeks. 2+ The reasons for the slower release may be multifaceted. The increase in the total amount of MgCO3 may lead to the 2+ In addition, higher total Mg monomer concentrations led to enhanced cross-linking between PCL and Mg, which may have caused slight changes in the thickness of the material, ultimately resulting in a nonlinear relationship between the concentration of Mg monomers and the sustained release rate of the material.
[0071] (3) Structural fiber parameters
[0072] The control group, 10% MgO / MgCO3 / PCL group, 20% MgO / MgCO3 / PCL group, and 30% MgO / MgCO3 / PCL group were treated with 2.5% glutaraldehyde for 6 h, then rinsed in deionized water three times, 30 min each time; and then dehydrated in gradient ethanol solutions (30%, 50%, 75%, and 100% ethanol) for 30 min each time. To enhance conductivity and contrast, a thin layer of platinum mixture was coated on the surface, and then the surface was analyzed using a scanning electron microscope (SEM; S-8010, Hitachi, Japan) with an accelerating voltage of 5 keV. Image analysis software (ImageJ; Cybernetics, Bethesda, MD, USA) was used to evaluate the structural fiber parameters.
[0073] The network structure of each group of fiber membranes was analyzed by scanning electron microscopy. Figure 3C As shown in the figure: the multi-gradient nanofiber membranes (10% MgO / MgCO3 / PCL group, 20% MgO / MgCO3 / PCL group, 30% MgO / MgCO3 / PCL group) are networks of nanofibers interconnected by MgO / MgCO3 nanoparticles. Figure 3D As shown: the average diameter of nanofibers in the control group (PCL) was 126.8±39.6 nm, that in the 10% MgO / MgCO3 / PCL group was 229.4±102.3 nm, that in the 20% MgO / MgCO3 / PCL group was 217.9±65.8 nm, and that in the 30% MgO / MgCO3 / PCL group was 253.6±92.3 nm.
[0074] (4) Mechanical properties
[0075] The contact angles of the control group, 10% MgO / MgCO3 / PCL group, 20% MgO / MgCO3 / PCL group, and 30% MgO / MgCO3 / PCL group were measured to further characterize the surface properties (wettability) of the MgO / MgCO3 / PCL multi-gradient nanofiber membrane.
[0076] Contact angle measurement using the ring pull-off method: During the measurement, the sample surface to be analyzed is suspended on a force sensor instead of a metal sheet and gradually immersed in the liquid phase. The force change is recorded to calculate the advancing contact angle value between the liquid and the solid surface. Subsequently, the solid sample is slowly withdrawn from the liquid phase while recording the force change to determine the receding contact angle value.
[0077] The measurement results are as follows Figure 3E As shown: the average contact angle of the control group (PCL) film was 124.9°±0.52°, that of the 10% MgO / MgCO3 / PCL group was 122.1°±1.61°, that of the 20% MgO / MgCO3 / PCL group was 120.2°±2.13°, and that of the 30% MgO / MgCO3 / PCL group was 120.9°±2.53°.
[0078] The above results show that there is no statistically significant difference in the contact angles between the membrane materials of each group, indicating that the interaction level between the membrane surface and the test liquid is comparable. This further confirms that the bioactive material mainly releases Mg 2+ Promotes peripheral nerve regeneration rather than its physical properties.
[0079] Test Example 2: Sciatic nerve defect animal experiment
[0080] The autologous nerve transplantation group was set as the blank control group; the PCL electrospun membrane was set as the PCL nerve conduit control group; the 10% MgO / MgCO3 / PCL multi-gradient nanofiber membrane of Example 1 was set as the 10% MgO / MgCO3 / PCL group, the 20% MgO / MgCO3 / PCL multi-gradient nanofiber membrane of Example 2 was set as the 20% MgO / MgCO3 / PCL group, and the 30% MgO / MgCO3 / PCL multi-gradient nanofiber membrane of Example 3 was set as the 30% MgO / MgCO3 / PCL group; the 10% MgO / MgCO3 / PCL group, the 20% MgO / MgCO3 / PCL group, and the 30% MgO / MgCO3 / PCL group were cut into 0.5 mm × 12 mm multi-gradient fibers, which were respectively the 10% MgO / MgCO3 / PCL nerve conduit group, the 20% MgO / MgCO3 / PCL nerve conduit group, and the 30% MgO / MgCO3 / PCL nerve conduit group.
[0081] 1. 10mm sciatic nerve defect model
[0082] Female SD rats (2 months old, weighing 200-250 g) were housed under standard laboratory conditions with a 12-h light / dark cycle, an ambient temperature of 25°C, and a humidity of 50%. The rats were randomly divided into five groups: autologous nerve transplantation group, PCL nerve conduit group, 10% MgO / MgCO3 / PCL nerve conduit group, 20% MgO / MgCO3 / PCL nerve conduit group, and 30% MgO / MgCO3 / PCL nerve conduit group.
[0083] The rats were anesthetized with 50 mg / kg body weight of sodium pentobarbital combined with isoflurane, and then microsurgery was performed by the same experienced surgeon.
[0084] 1) Fix and disinfect the surgical site (right thigh), then create an incision of approximately 4 cm parallel to the lower edge of the femur; carefully expose the sciatic nerve through this incision using a surgical microscope;
[0085] 2) In the autologous transplantation group, 10 mm of the sciatic nerve was resected, everted, and reinserted, and the autologous nerve was fixed to the adventitia of the proximal and distal ends of the nerve using 10-0 monofilament nylon sutures;
[0086] In the PCL nerve catheter group, 10% MgO / MgCO3 / PCL nerve catheter group, 20% MgO / MgCO3 / PCL nerve catheter group, and 30% MgO / MgCO3 / PCL nerve catheter group, the distal end of the exposed sciatic nerve was first cut off, and then the nerve stump was moved 1mm proximal to the 12mm nerve catheter to form a 10mm gap, and then fixed in place with 10-0 nylon sutures. Multi-gradient fiber membranes cut into 0.5mm×12mm containing 10%, 20%, and 30% MgO / MgCO3 / PCL were inserted into the nerve catheters (4 per catheter, and the inner layer of the multi-gradient fiber membrane was attached to the inner wall of the nerve catheter), and the other end was connected to the distal end of the nerve; the diameter of the catheter (about 2mm) was anastomosed with the sciatic nerve;
[0087] 3) Use 4-0 silk suture to suture the skin wound.
[0088] 2. Gait analysis and neurophysiological monitoring to evaluate nerve regeneration and motor function recovery.
[0089] Footprints were captured at 2, 4, 6, and 12 weeks after surgery to assess the functional recovery of peripheral nerves ( Figure 4A,B). The SFI (Sciatic Function Index) is a well-established and sophisticated method for assessing sciatic nerve function in rats. Calculating the SFI provides a non-invasive method for assessing the degree of motor function recovery of target muscles after injury to the sciatic nerve or its branches. SFI values range from 0 (indicating normal values) to -100 (indicating complete nerve rupture). Lower absolute SFI values indicate better recovery of nerve function. Rats in all five experimental groups showed improvement in overall motor function over time.
[0090] The results showed that the autologous transplant group had the lowest absolute SFI value among the five groups, followed by the 10% MgO / MgCO3 / PCL group. No statistically significant differences were observed between the other three groups. Electrophysiological evaluation was performed 12 weeks after surgery. CMAP (compound muscle action potential) was recorded by placing signal receiving electrodes on the gastrocnemius muscles of the five groups of rats. The autologous transplant group showed the highest CMAP amplitude, followed by the 10% MgO / MgCO3 / PCL group. No statistically significant differences were observed between the other three groups ( Figure 4C ,D).
[0091] After nerve injury, muscle atrophy was observed in the affected gastrocnemius (triceps calf muscle) in all five groups, and nerve regeneration improved over time. Gastrocnemius muscle samples were collected 12 weeks after surgery for Masson's trichrome staining to assess muscle structure ( Figure 4E ). Among the five experimental groups, the autologous transplant group showed the best results, as shown by an increase in muscle fiber cross-sectional area, a decrease in collagen fiber area, and a decrease in the percentage of collagen fiber area. Among the other four groups, the 10% MgO / MgCO3 / PCL group had the largest muscle fiber cross-sectional area, the largest decrease in collagen fiber area, and the lowest percentage of collagen fiber area. However, no significant differences were observed between the 20% MgO / MgCO3 / PCL, 30% MgO / MgCO3 / PCL, and PCL nerve conduit groups. The mean values of the percentage of collagen fiber area in the five groups were: 12.2%±2.3% in the autologous transplant group, 26.1%±5.5% in the PCL group, 16.5%±4.7% in the 10% MgO / MgCO3 / PCL group, 20.1%±3.3% in the 20% MgO / MgCO3 / PCL group, and 21.1%±4.0% in the 30% MgO / MgCO3 / PCL group ( Figure 4F -H).
[0092] 3. At 6 and 12 weeks after surgery, 4% paraformaldehyde solution was perfused through the rat circulatory system to obtain regenerated nerves.
[0093] like Figure 5BAs shown, 6 weeks after surgery, nerve continuity was observed to be restored, and regenerated nerve tissue was visible in the nerve conduit of the experimental group. The nerve graft was evenly divided into three parts: proximal, middle, and distal. At 12 weeks after surgery, a 2 mm long middle nerve specimen was obtained for histological evaluation of the regenerated nerve.
[0094] 1) The cross-sections of the middle region were cut into 7 μm thickness using a Leica CM3050S slicer. The sections were stained with hematoxylin-eosin. Five random field images of each section were then analyzed.
[0095] Hematoxylin-eosin staining was used to evaluate the newly formed nerve fibers in each group, and the diameter of the newly formed nerves was measured in the cross section. Figure 5C and 5D As shown in the figure, the size of the autologous nerve transplantation group was the most significant and statistically significant, followed by 10% MgO / MgCO3 / PCL, 20% MgO / MgCO3 / PCL, 30% MgO / MgCO3 / PCL, and PCL nerve conduit. The results showed that the nerve repair effect of the three groups implanted with MgO / MgCO3 / PCL multi-gradient nanofiber conduits was significantly better than that of the negative control group (PCL nerve conduit). 2+ The 10% MgO / MgCO3 / PCL group with the lowest concentration had the best repair effect. In the first 6 weeks of nerve regeneration, the 10% MgO / MgCO3 / PCL group showed higher Mg 2+ Effective release rate.
[0096] 2) Toluidine blue staining and transmission electron microscopy were used to observe the distal tissue structure of the nerve graft. The 2 mm section of the regenerated nerve was treated with 2.5% glutaraldehyde for 2 h and then fixed with 1% osmium tetroxide for 1.5 h. The tissue samples were dehydrated in an ethanol series, embedded in Epon 812 resin (Ted Pella, Redding, CA, USA), and then cut into 1 μm semi-thin sections and 50 nm ultra-thin sections. The semi-thin sections were stained with toluidine blue solution, and the ultra-thin sections were examined by TEM (JEOL, Tokyo, Japan). Five areas were randomly selected from each area for image acquisition. The diameter of myelinated axons and the thickness of myelin sheaths were measured using Photoshop CS6 software (Adobe Systems). The G ratio is the ratio of axon diameter to fiber diameter. Five random field photos of each ultra-thin nerve section were analyzed, and statistical analysis was performed on five samples in each group.
[0097] like Figure 5E As shown, remyelination of regenerated nerves was evaluated by toluidine blue staining and TEM analysis. Nerve graft specimens were collected 12 weeks after surgery, and cross-sections of the distal 2 mm of the regenerated nerves were examined.
[0098] The diameter and number of myelinated axons were assessed in TEM images ( Fig. 5F , G), and the thickness of the new myelin sheath ( Figure 5H In addition, the G ratio was calculated to measure the maturity of myelinated axons ( Fig.5I ). Among the groups, myelin regeneration was obvious in the autologous nerve transplantation group, and the myelin sheath around the regenerated axons was significantly thickened. Compared with the control group, the number and size of myelinated axons and the thickness of myelin sheath in the 10% MgO / MgCO3 / PCL nerve conduit group were significantly increased (p<0.05). Compared with the 30% MgO / MgCO3 / PCL nerve conduit group and the PCL nerve conduit group, the thickness of the newly formed myelin sheath in the 20% MgO / MgCO3 / PCL nerve conduit group was significantly improved (p<0.05). There was no statistically significant difference in nerve diameter, number of myelinated axons and G ratio among the 20% MgO / MgCO3 / PCL nerve conduit group, the 30% MgO / MgCO3 / PCL nerve conduit group and the PCL nerve conduit group (p>0.05). These results indicate that Mg 2+ It plays an important role in promoting axonal myelination. Schwann cells are mainly involved in the process of nerve regeneration, and the MgO / MgCO3 / PCL multi-gradient fibers continuously release Mg. 2+ It is possible that the Shh / Ptch1 / Gli1 axis affects the phenotypic transformation of Schwann cells in the middle and late stages of nerve regeneration and promotes the repair of peripheral nerve defects. 2+ Balance is essential to support Schwann cell function and promote efficient nerve regeneration.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A multi-gradient nanofiber membrane, characterized in that: It comprises an inner layer, a middle layer and an outer layer; the inner layer comprises a magnesium-containing compound and polycaprolactone in a mass ratio of (0.12-0.36):1; the middle layer comprises a magnesium-containing compound and polycaprolactone in a mass ratio of (0.1-0.3):1; the outer layer comprises a magnesium-containing compound and polycaprolactone in a mass ratio of (0.08-0.24):
1.
2. The multi-gradient nanofiber membrane according to claim 1, characterized in that: The magnesium-containing compounds include MgO and MgCO3.
3. The multi-gradient nanofiber membrane according to claim 2, characterized in that: The mass ratio of MgO and MgCO3 in the inner layer is (0.3-0.7):1; the mass ratio of MgO and MgCO3 in the middle layer is (0.8-1.4):1; the mass ratio of MgO and MgCO3 in the outer layer is (1.5-2.5):
1.
4. The multi-gradient nanofiber membrane according to claim 1, characterized in that: The mass percentage of magnesium in the inner layer is 12.57%-24.54%; the mass percentage of magnesium in the middle layer is 11.42%-20.46%; and the mass percentage of magnesium in the outer layer is 9.43%-19.63%.
5. The method for preparing the multi-gradient nanofiber membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) adding the polycaprolactone into a solvent and stirring to obtain a mixed solution; (2) adding the magnesium-containing compound to the inner layer, the middle layer and the outer layer respectively, stirring evenly, and obtaining the electrospinning solutions of the inner layer, the middle layer and the outer layer respectively; (3) The obtained electrospinning solutions of the inner layer, the middle layer and the outer layer are used for electrospinning, and the electrospinning is stacked layer by layer to form an electrospun membrane with a three-layer composite structure, that is, a multi-gradient nanofiber membrane.
6. The preparation method according to claim 5, characterized in that: In step (1), the solvent is trifluoroethanol; the mass volume ratio of the polycaprolactone to the solvent is 5%-15% g / mL.
7. The preparation method according to claim 5, characterized in that: In step (3), the electrospinning uses a high voltage electric field of 10kv-20kv.
8. A nerve conduit, characterized in that: The multi-gradient nanofiber membrane according to any one of claims 1 to 4 is built in.
9. The nerve guide according to claim 8, characterized in that: The inner layer of the multi-gradient nanofiber membrane faces the inner wall of the nerve conduit.
10. Use of the multi-gradient nanofiber membrane according to any one of claims 1 to 4, or the nerve conduit according to claim 8 or 9 in any of the following fields, characterized in that: include: i. Preparation of preparations for promoting nerve regeneration; ii. preparing a nerve conduit for promoting nerve regeneration; iii. Preparation of preparations for peripheral nerve defect repair; iv. Preparation of nerve conduits for peripheral nerve defect repair; v. Treatment of peripheral nerve defects for purposes other than diagnosis or treatment of other diseases.
Citation Information
Patent Citations
Multilayer gradient biofilm and preparation method thereof
CN110193098A
Preparation process of electrospun nanofibers
CN110257955A
Guided tissue regeneration membrane as well as preparation method and application thereof
CN113117150A
Gradient material for promoting cartilage calcification layer repair and preparation method
CN113456885A
Power generation control system and method of fuelcell
KR1020220031152A